2017
DOI: 10.1016/j.mmcr.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic hip joint infection with Aspergillus terreus : A clinical case and a review of the literature

Abstract: Fungal periprosthetic joint infections due to Aspergillus species are rare but are associated with significant cost and morbidity. We present a case of Asperigillus terreus prosthetic joint infection of the hip. The patient was successfully treated with a prolonged course of systemic antifungals along with surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Although tissue was not sent for histopathology in our case, it is an important tool to define the diagnostic significance of positive culture results when contamination is suspected. Aspergillus terreus infections may produce high levels of serum galactomannan; however, serum galactomannan was negative in our case and the other PJI case reported in the literature due to A terreus [ 18 ]. This is likely because these infections are limited to the joint and are not disseminated.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Although tissue was not sent for histopathology in our case, it is an important tool to define the diagnostic significance of positive culture results when contamination is suspected. Aspergillus terreus infections may produce high levels of serum galactomannan; however, serum galactomannan was negative in our case and the other PJI case reported in the literature due to A terreus [ 18 ]. This is likely because these infections are limited to the joint and are not disseminated.…”
Section: Discussioncontrasting
confidence: 64%
“…A review article on Aspergillus osteomyelitis (excluding septic arthritis and PJI) by Gamaletsou et al [ 16 ] demonstrated A terreus as the etiology of infection in only 3% (5 of 180) of the cases. There are only a handful of PJIs secondary to A terreus reported to date [ 14 , 17 , 18 ]. To the best of our knowledge, our case is the first case of a finger PJI secondary to A terreus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiles [ 7 ] or Aspergillus spp. [ 8 ], and in a small percentage of cases there may be a concomitant bacterial infection [ 3 ]. When the fungus encounters the implant surface, it develops a complex biofilm which displays potent resistance to antimicrobial therapy and protects the community of microbes from the immune response, which is the cause for the high persistence of the infection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus terreus is a medically important pathogen associated with life-threatening states, ranging from cystic fibrosis, aspergillomas, spondylodiscitis, and periprosthetic hip-joint infection in immunocompetent hosts and lethal invasive disease in immunocompromised individuals. 1 – 4 An upsurge in the mortality rate of 74%–92% in transplant recipients suffering from invasive aspergillosis has been reported. 5 , 6 It is now understood that invasive aspergillosis sufferers often have higher incidence of cancer and organ transplantation, 7 an indication that Aspergillus infections could lead to sequential development of other diseases.…”
Section: Introductionmentioning
confidence: 99%